Stable Gastric Pentadecapeptide BPC 157-NO-system Relation - Sikiric, Predrag; Seiwerth, Sven; Rucman, Rudolf; Turkovic, Branko; Stancic Rokotov, Dinko; Brcic, Luka; Sever, Marko; Klicek, Robert; Radic, Bozo; Drmic, Domagoj; Ilic, Spomenko; Kolenc, Danijela; et al. (Current Pharmaceutical Design, 2014)
We reviewed stable gastric pentadecapeptide BPC 157-NO-system-relation, its close participation in Moncada's (maintained vascular integrity, platelets control) homeostatic healing response of NO-system to injury. Namely, BPC 157’s particular healing effect also affects all events after vascular integrity loss (dependent on circumstances, it reduces either thrombosis (abdominal aorta anastomosis) or bleeding/thrombocytopenia (amputation, heparin, warfarin, aspirin)) and in a series of different injurious models, acute and chronic, BPC 157 consistently advances healing after severe injuries in various tissues spontaneously unable to heal; stimulates egr-1 and naB2 genes; exhibits high safety (LD1 not achieved)). Hypothesis, that BPC 157 (since formed constitutively in the gastric mucosa, stable in human gastric juice, along with significance of NO-synthase and the basal formation of NO in stomach mucosa, greater than that seen in other tissues) exhibits a general, effective competing both with L-arginine analogues (i. e., L-NAME) and L-arginine, and that this has some physiologic importance (NO-generation), later, practically supports its beneficial effects illustrating BPC 157 and NOsystem mutual (with L-NAME/L-arginine; alone and together) relations in (i) gastric mucosa and mucosal protection, following alcohol lesions, in cytoprotection course, NO-generation, and blood pressure regulation; (ii) alcohol acute/chronic intoxication, and withdrawal; (iii) cardiovascular disturbances, chronic heart failure, pulmonary hypertension, and arrhythmias; (iv) disturbances after hypokalemia and hyperkalemia, and potassium-cell membrane dysfunction; and finally, in (v) complex healing failure, proved by the fistulas healing, colocutaneous and esophagocutaneous. However, how this advantage of modulating NO-system (i. e., particular effect on eNOS gene), may be practically translated into an enhanced clinical performance remains to be determined.
Keywords: Thrombosis